Penurunan Total Coliform Mata Air dengan Desain Biofilter Limbah Organik - Djawa, Viennye Wilhelmina; Sarifan, Gracyana Putri; Tahu, Maria Astin Rosari; Semiun, Chatarina Gradict (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Unconserved springs tend to be polluted by various organic wastes. Accumulation of organic waste causes water to be contaminated with coliform bacteria, thus reducing water quality. Biofilter technology can be applied to reduce the number of coliform bacteria. This study aimed to determine the ability of BioFilter K4Ser-Col (moringa seeds, rice husks and kesambi charcoal) to reduce total coliform in spring water. The research location was at the Riumata Spring, Nekbaun village, West Amarasi sub-district, Kupang district. The work consisted of preparing the BioFilter K4Ser-Col media, taking water samples, and testing MPN coliform. MPN coliform testing was done twice before and after the water filtration on the BioFilter K4Ser-Col media. The study's results showed a decrease in the MPN value before and after filtering. The MPN coliform value before filtering was 1600 MPN/100 mL. After filtered water on the BioFilter K4Ser-Col media, it decreased to 23.23 MPN/100 mL. This value had met the national water quality standards for the class I category based on PP No. 22 of 2021. Thus, the use of BioFilter K4Ser-Col media could greatly reduce the number of coliform bacteria in water.